Clinical Study of Restless Leg Syndrome Accompanied by Psychological Symptoms Induced by High-Dose Treatment With Madopar - Zhu, Lei; Li, Jing; Ren, Chongyang; Zhang, Mei; Xue, Min; Yu, Chuanqing; Zhang, Weili (Frontiers in Psychiatry, 2019)
Objectives: Some neurological disorders show an indistinguishable psychological symptom at an early stage, especially when accompanying with jitter similar to Parkinson's disease. During the dopamine replacement therapy, some patients represent restless leg syndrome (RLS)-like symptoms. We aimed to analyze the treatment strategy and prognosis of RLS caused by large-dosage madopar. Methods: Nine cases showing symptoms of anxiety, depression and somatization were recruited due to misdiagnosis of Parkinson's disease and taking a large dose of madopar. Clinical data were collected and strategies of treatment and prognosis were analyzed. Results: Seven patients had different degree of anxiety and depressive disorder, and the other 2 cases were misdiagnosed as Parkinson's disease. During madopar treatment, these cases showed gradually aggravated symptoms of acid swelling, numbness and pain, and other indescribable sensory abnormalities in both lower extremities, which spread to both upper extremities in a few patients. Among 7 patients, the symptoms of anxiety, depression, insomnia and somatization significantly worsen during time. The average time for 9 patients from taking madopar to the appearance of RLS was 2.6±0.6 months, the average time to clinic diagnosis was 18.17±9.40 months, and average dosage of madopar was 1.44±0.21 g per day. A strategy with gradually reducing the madopar dosage and giving a small dose of long-acting dopamine preparation were used, which greatly alleviated the symptoms after following up for 3 months. Conclusion: Large dosage madopar can cause RLS-like symptoms accompanied by anxiety, depression, insomnia and other mental symptoms, which should be highly paid attention by clinicians.